WHAT KEEPS COFFEE CUSTOMERS COMING BACK? THE ROLES OF CUSTOMER RELATIONSHIP MANAGEMENT, CUSTOMER ENGAGEMENT, AND CAFÉ ATMOSPHERE - Ade Wahyudistira; E.R Taufik; Liza Mumtazah Damarwulan (RADJA PUBLIKA, 2026)
Purpose. Retaining customers in the café segment is increasingly difficult as switching costs approach zero and competing outlets converge on product quality. This study asks why some customers return and disentangles two routes to retention that the prevailing literature has largely treated in isolation: a relational route operating through customer relationship management (CRM) and customer engagement, and an experiential route operating through the café atmosphere. Design/methodology/approach. Survey data from 200 patrons of the coffee shop were analysed with partial least squares structural equation modelling (PLS-SEM), incorporating a mediation test for engagement and a moderation test for atmosphere on the CRM–retention link. Findings. CRM exerts a small but significant direct effect on retention (β = 0.152, p = 0.027), and a larger share of its influence is channelled through customer engagement (indirect β = 0.224, p < 0.001) a complementary (partial) mediation in which engagement remains the dominant pathway, accounting for approximately 60 per cent of CRM's total effect, without eliminating a direct relational payoff. Café atmosphere is the single strongest driver of retention (β = 0.468, p < 0.001), exceeding both components of the relational route, while its hypothesised amplification of the CRM–retention link is not supported (β = 0.043, p = 0.459). The model explains a moderate share of retention variance (R² = 0.691). Originality/value. The study reframes CRM as an antecedent whose retention payoff is only partly direct and is substantially amplified when it is psychologically converted into engagement, and it shows that the relational and experiential routes operate largely in parallel rather than synergistically an environmental dominance that has practical consequences for how independent cafés allocate scarce resources.